FIQIH MINORITAS MUSLIM DALAM BERINTERAKSI KEPADA NEGARANYA - Imam Taufik Alkhotob Alkhotob (Jurnal Da'wah: Risalah Merintis, Da'wah Melanjutkan, 2021)
When the Muslim community lives in a country as a minority, they usually stay active with limited space and movement. This is because they come with different religions and cultures. As a minority, Islam regulates how they should interact with the country where they live. Through qualitative methodology and descriptive analysis writing, the author will explain the forms of interaction that must be carried out. The result is six things; Minority Muslims are obliged to preach Islam to the Community and the State, Maintain the implementation of the main religious syari'at for individuals in the life of the state, Maintain the rules of the shari'ah that have been agreed upon regarding its halalness and prohibitions, even though the State legalizes it, Obligation to be involved in the process building the State and resolving the problems of the State, the obligation to maintain relations between fellow citizens of the State and not to carry out rebellion against the State unless they have the ability and after seeing the magnitude of the Maslahat caused